Interactions of the Westerlies and Asian Summer Monsoon Since the Last Deglaciation in the Northeastern Qinghai‐Tibet Plateau. Issue 11 (14th November 2022) - Li, Yu; Peng, Simin; Hao, Lu; Zhou, Xueru; Li, Haiye
Abstract: The Asian summer monsoon (ASM), controlled by tropical ocean‐atmosphere systems, and the westerlies, directly linked to high‐latitude climates, interact in mid‐latitude East Asia. Located at a climate junction, the northeastern Qinghai‐Tibetan Plateau (QTP) is a sensitive zone for the interaction of the westerlies and ASM. In the current work, we present a new loess data set from the northeastern QTP since the last deglaciation, including grain size, stable isotope (δ 13 Corg and δ 18 Ocarb ), total organic carbon, total nitrogen, magnetic susceptibility, and mineral composition. The PMIP3‐CMIP5 multi‐model ensemble and TraCE‐21ka transient simulation are used synthetically to analyze climate mechanisms. All proxies suggest instable glacial climate and stable interglacial climate in the northeastern QTP. The coarser grain size during the last deglaciation compared with the Holocene reflects intensified westerlies controlled by the weakening of Atlantic Meridional Overturning Circulation and existing ice sheets. More positive δ 18 Ocarb values during abrupt cooling events [Heinrich event 1 (H1) and the Younger Dryas (YD)] indicate the effect of a weakened monsoon triggered by the low‐latitude solar insolation and sea surface temperature. Therefore, the anti‐phase pattern between the ASM and westerlies is the primary reason for differences in climate stability. Moreover, low temperature favors the predomination of C3 plants and the development of permafrost, leading to more negative δ 13 Corg values and fine grain size during the H1 and YD. Taken together, the anti‐phase relationship between the westerlies and ASM emphasizes the complicated dynamic characteristics of atmospheric systems in the mid‐latitudes and the challenges for future predictions. Plain Language Summary: The relationship between the westerly circulation and Asian summer monsoon (ASM) system at different timescales is still under discussion in both meteorology and paleoclimatology communities in recent years. Due to the huge differences in the dynamic mechanisms of the two circulation systems, relevant previous studies on millennial‐scale climate change distinguished the westerlies and ASM based on various paleoclimate indicators, and rarely defined the meaning and specific process of their interaction. Under global warming, clarifying the interactions of the westerlies and ASM is critical to understanding the pattern and mechanism of climate change in mid‐latitudes. Therefore, the comprehensive analysis of surface sediments, paleoclimate records, and paleoclimate simulation on long‐term timescales are conducted in the northeastern Qinghai‐Tibetan Plateau which is a sensitive zone for the synergistic effect of the westerlies and ASM. The results show that the ASM mainly affects the Holocene climate, while the westerlies dominate during the last deglaciation in the northeastern Qinghai‐Tibetan Plateau. The anti‐phase pattern between the ASM and westerlies leads to instable glacial climate and stable interglacial climate. Key Points: Anti‐phase pattern between the Asian summer monsoon and westerlies triggers the difference in climate stability during glacial and interglacial periods Coarser grain size during the last deglaciation compared with the Holocene reflects intensified westerlies linked to weakening Atlantic Meridional Overturning Circulation More positive δ 18 Ocarb values during abrupt cooling events (H1 and Younger Dryas) indicate the influence of the weakened monsoon